Transformational Leadership and Cultural Dynamics in the Pharmaceutical Sector - Senturk, Mehmet (Journal of Policy Options, 2023)
This study investigates the effect of transformational leadership behavior on organizational culture within a pharmaceutical company by analyzing data collected from 100 employees in the production sector. The aim is to determine statistically significant relationships between transformational leadership and various aspects of organizational culture, providing insights into how leadership styles can influence and shape the work environment and cultural dynamics within the company. The results of the study support the hypotheses, revealing that transformational leadership behavior has a positive and significant correlation with various components of organizational culture. Specifically, the findings indicate that transformational leadership is positively associated with long-term/short-term orientation, masculinity/femininity, power distance, individualism/collectivism, and uncertainty avoidance. These correlations suggest that transformational leaders significantly influence these cultural dimensions, thereby shaping the overall organizational environment in meaningful ways.